Pengaruh Marketing Mix Terhadap Keputusan Memilih Perguruan Tinggi - Anton Widio Pratomo (Forum Dosen Indonesia, 2022)
The purpose of this study was to examine and analyze the effect of marketing mix elements which include product (X1), price (X2), place (X3), promotion (X4), people (X5), process (X6), and physical evidence (X7). and the effect of the overall (simultaneous) marketing mix on the student's decision to choose the Bogor Unity IBI campus. This study uses primary data through a survey of 97 active IBI Unit students in the even semester of the 2019/2020 academic year. The collected data is processed and analyzed using SPSS software. From the results of this study indicate that; (1) Product has a positive and significant effect on students' decisions to choose to study at IBI Kesatuan Bogor; (2) price has no effect on students' decisions to choose to study at IBI Bogor Unity; (3) place does not affect the student's decision to choose to study at IBI Kesatuan Bogor; (4) promotion has a positive and significant effect on student decisions to choose to study at IBI Kesatuan Bogo; (5) people have a positive and significant effect on students' decisions to choose to study at IBI Kesatuan Bogor; (6) the process does not affect the student's decision to choose to study at IBI Kesatuan Bogor; (7) has a positive and significant effect on student decisions to choose to study at IBI Kesatuan Bogor; (8) Overall variable X (marketing mix) has a positive and significant effect on student decisions to choose to study at IBI Kesatuan Bogor of 77.1%. Keywords: product, price, place, promotion, people, process, physical evidence